2013
DOI: 10.3329/bjp.v8i2.13690
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of nattokinase from UV mutated Bacillus sp.

Abstract: In the recent years, nattokinase is one of the most-often employed among the several thrombolytic agents used clinically, particularly because of its lower cost comparing to other thrombolytic agents. In the present research work, Bacillus sp. was isolated from the heterogeneous microbial population present in the soil sample and screened for the production of nattokinase. The production of the enzyme was carried out using two different media (with and without shrimp shell substrate). Nattokinase activity (clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…The production of NK has been enhanced by physical and chemical mutagenesis. The results of the present study are supported by existing reports on enhanced production of NK by UV-mutated Bacillus spp., which significantly demonstrated better activity compared to the wild type strain ( 22 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The production of NK has been enhanced by physical and chemical mutagenesis. The results of the present study are supported by existing reports on enhanced production of NK by UV-mutated Bacillus spp., which significantly demonstrated better activity compared to the wild type strain ( 22 ).…”
Section: Discussionmentioning
confidence: 89%
“…In the Holmstrom method, the extent of lyses was checked after the coagulation of blood, in order to determine enzyme activity. One unit of enzyme activity was defined as the minimum amount of enzyme at which blood clot lysis occurred completely ( 18 , 22 , 23 ). Thereby, it can be concluded from the results that 60 and 90 minutes of exposure time to UV was the most effective in producing favorable mutation that enhanced NK production with a higher activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P. aeruginosa CMSS grown on 1% sucrose supplemented medium, showed maximum NK activity (3930 U mL -1 ) than the strain grown in medium with other carbon source (Fig.3 d). The results of the present study are supported by existing reports on enhanced production of NK by UV-mutated Bacillus spp., which significantly demonstrated better activity compared to the wild type strain 13 . The previous studies on NK production after optimization reported that the maximum NK activity from Bacillus sp.…”
Section: Optimization Studiesmentioning
confidence: 90%
“…The heated plasma was then cooled to optimum temperature and added to nutrient agar and mixed well by shaking (15ml of nutrient agar medium was prepared, 10 ml of plasma was added) and poured into petri dishes. Well diffusion was also used in this technique [17]. [18,19] with minor modification.…”
Section: -Human-heated Plasma Agar Testmentioning
confidence: 99%